Evaluation of the risk factors of depressive disorders comorbid with obstructive sleep apnea - Cai LQ (Neuropsychiatric Disease and Treatment, 2017)
Liqiang Cai,1 Luoyi Xu,1 Lili Wei,1 Yi Sun,2 Wei Chen1,3 1Department of Psychiatry, Sir Run Run Shaw Hospital, Collaborative Innovation Center for Brain Science, Zhejiang University School of Medicine, 2Department of Electroencephalogram, Sir Run Run Shaw Hospital, 3Key Laboratory of Medical Neurobiology, Chinese Ministry of Health, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China Objective: Overlap of obstructive sleep apnea (OSA) complicates diagnosis of depressive disorder and renders antidepressant treatment challenging. Previous studies have reported that the incidence of OSA is higher in patients with depression than in the general population. The purpose of this article was to investigate clinical risk factors to predict OSA in depression disorders.Methods: A total of 115 patients diagnosed with major depressive disorder (MDD) and bipolar disorder (in a major depressive episode), who underwent overnight polysomnography, were studied retrospectively. They were divided into two groups: non-OSA and OSA. The patients who had apnea–hypopnea index (AHI) <5 were defined as the non-OSA group, whereas the OSA group was defined as those with an AHI ≥5. Logistic regression was used to analyze the association among AHI and clinical factors, including sex, age, body mass index (BMI), Hamilton Depression Rating Scale (HAMD), Hamilton Anxiety Rating Scale, Pittsburgh Sleep Quality Index (PSQI), and diagnosis (MDD or bipolar disorder [in a major depressive episode]).Results: In 115 patients, 51.3% had OSA. Logistic regression analysis showed significant associations between AHI and diagnosis (MDD or bipolar disorder [in a major depressive episode]), BMI, HAMD, and PSQI (P<0.05).Conclusion: The findings of our study suggested that the rate of depression being comorbid with OSA is remarkably high and revealed that there is a high rate of undetected OSA among depressive disorder patients and untreated OSA among mood disorder patients. The clinical risk factors (diagnosis [MDD or bipolar disorder {in a major depressive episode}], BMI, HAMD, and PSQI) could predict AHI or OSA diagnosis and contribute to OSA screening in depressive disorder patients.Keywords: major depressive disorder, polysomnography, obstructive sleep apnea, risk factors, apnea–hypopnea index